Keberadaan Komisi Yudisial Dalam Rangka Membangun Peradilan yang Bersih dan Berwibawa - Fontian Munzil (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2017)
The main problem in this research: first, how far does the existence of the Judicial Commission realize a dignified Judge? Second, how is the Judicial Commission strengthening as an effort to build a clean and authoritative judiciary?The research method used is normative juridical to analyze research data. Data was collected through a review of data obtained from secondary data, primary and secondary legal materials. Secondary data research on legislation by means of vertical and horizontal synchronization, including conducting legal comparison methods with other countries. The results of the study found, first, that the legislation has largely regulated the position of the Judicial Commission but in practice it cannot be fully implemented because of the lack of regulation and technical understanding with the Supreme Court as the technical understanding of the verdict as a basis for alleged violations of the code of ethics. Second, strengthening the existence and contribution of the Judicial Commission by giving practical contributions to the Supreme Court in the form of increasing the competence and welfare of judges with the Judicial Commission budget, and establishing a joint task force with other law enforcement agencies in order to maintain and uphold the honor, dignity and conduct of Judges and form representatives of the Judicial Commission in the region.